Dietary polyphenols as photoprotective agents against UV radiation. (March 2017) - Hu, Shuting; Zhang, Xinchen; Chen, Feng; Wang, Mingfu
Highlights: Introduced the major types of DNA photolesions after UV irradiation. Discussed DNA repair mechanism and cellular defense systems after UV irradiation. Summarized the photoprotective effects of selected dietary polyphenols. Abstract: Ultraviolet radiation in the sunlight is able to penetrate the atmosphere and cause cumulative injury to the skin. Clinically the photoaging component of skin aging accounts for the development of sunburn, tanning and wrinkling in sun-exposed areas. In addition, chronic exposure of the skin to UV radiation is a major etiologic risk factor to non-melanoma skin cancers. Recently, dietary polyphenols have been suggested as potential candidates to protect the skin from harmful effects of UV irradiation. Oral or topical treatment of some well-known dietary polyphenols such as green tea polyphenols, has great potential to prevent damages such as UV-induced sunburn response, immunosuppression and photoaging. This review introduces the major types of DNA photolesions after UV-irradiation, the following repair mechanisms and cellular defense systems. This review also summarizes the photoprotective effects of selected dietary polyphenols against UV-induced oxidative stress, DNA damage and skin inflammation.